Single phase full bridge inverter using Sinusoidal Pulse Width Modulation (SPWM) switching technique / Nordin Mohd Jalil - Mohd Jalil, Nordin (2012)
This thesis describes about the development of single phase inverter for photovoltaic (PV) application circuit with Sinusoidal Pulse Width Modulation (SPWM) as switching technique. This project consists of two parts simulation model and experimental testing. Matlab simulink is used to simulate the circuit with SPWM signal output. The simulation results are presented and discussed. A prototype of single phase inverter is constructed using SPWM switching technique controlled by PIC16F877A. The controller which is the driver of the circuit concept also will be implemented in order to monitor and control the output voltage, so that the input and output voltage is always in synchronous and stable condition based on the duty cycle.